A Retrospective Claims-Based Study Evaluating Clinical and Economic Burden Among Patients With Moderate to Severe Osteoarthritis Pain in the United States - Patricia B. Schepman; Sheena Thakkar; Rebecca L. Robinson; Craig G. Beck; Deepa Malhotra; Birol Emir; Ryan N. Hansen (Journal of Health Economics and Outcomes Research, 2022)
# Background There has been limited evaluation of medication adherence, healthcare resource utilization (HCRU), and healthcare costs over time in patients with osteoarthritis (OA), and stratification by pain severity level has not been reported. Assessing such longitudinal changes may be useful to patients and healthcare providers for tracking disease progression, informing treatment options, and employing strategies to optimize patient outcomes.